Effects of Two Insecticides on Survival, Growth and Emergence of Chironomus riparius Meigen - Agra, Ana R.
Effects of chlorpyrifos and cypermethrin on the survival, growth and emergence of Chironomus riparius were determined on a life-cycle study. Although neither cypermethrin nor chlorpyrifos affected larval survival or growth, a decrease in the number of emerged midges and in the number of females over males, as well as in female biomass, were found for both insecticides. The results from this study indicate that multiple biological endpoints and extended periods of exposure are needed in order to achieve a better screening of insecticide toxicity.